ANALISIS KEBIJAKAN TATANIAGA BERAS INDONESIA - Arifin, Bustanul; Suparmin, .; Sugiyono, . (Indonesian Journal of Socio Economics)
This study examines marketing system of rice, emphasizing on horizontal and vertical integration of paddy and rice, both at regional and world market. The study also anlyzes price stabilization pf appady at farm level and rice at consumer level, and examines domestic buffer stocks managed by rice. Econometric metdhos of vector autoregressive (VAR) and vector error correction model (VECM) are emplyed in this study. The results show that marketiung system of rice in Indonesia is very straightforward, involving commodity flow from paddy farmers, collector traders, rice millers, wholesalers, distributors, retail traders, and rice consumers. Rice markets in five major regions in Sumatra, Java, Kalimantan, Sulawesi, and Bali Nusa Tenggara showed horizontal market integration during the New Order regime (1968-1997)m albeit not in full integration. Rice markets were segmented during free-trade period (1998-2000), and during a managed-open market period (2001-2004). Vertical integration between paddy and ricve market only occurred during the New Order. Also, during that period, paddy price was relatively more stable than rice price in all three regimes. The study suggests that regulation in rice import should be continued, and policies on production improvmenet, land reform, and food diversification deserve more budget allocation. The government should develop regional price procurement system and strengthen rice buffer stock at regional level.